The Effect of Half Wave Pulsed Current Charging on Age and Capacity Fade for Lithium-ion Batteries - Muhammed Reşit ÇORAPSIZ (Journal of Innovative Science and Engineering)
This study proposes a new pulsed charging current technique to reduce aging and capacity losses in lithium-ion battery cells. The charging techniques developed to minimize aging and capacity losses are critical for battery cells with longer life cycles and higher energy efficiency. Continuous Current – Continuous Voltage charging (CC-CV), Positive Pulsed Current (PPC), and proposed Alternating Half Wave Pulsed Current (AHWPC) techniques were tested on a 12.8V-40Ah Li-ion battery. In PPC and AHWPC techniques, the pulse frequency of the charging current is chosen as f_(i_ch )=1 Hz. The average value of the charging current for PPC and AHWPC techniques is calculated based on the CC-CV technique. The aging and capacity losses caused by the three charging techniques in the battery were measured in five different scenarios: at various temperatures, different discharge currents, and different depths of discharge (DoD). Using the AHWPC technique, improvements of 45.93%, 46.57% and 46.29% were achieved in cell aging compared to the CC-CV technique at temperatures of 20°C, 30°C and 40°C, respectively. According to the results, the proposed AHWPC technique performed better than the PPC and CC-CV techniques in all test conditions.